2022
DOI: 10.1155/2022/7502239
|View full text |Cite|
|
Sign up to set email alerts
|

Informatization Teaching Mode of Vision Sensor Digital Image and Fusion Association Rule Mining Algorithm

Abstract: Informatization teaching mode emerged under the tide of informatization development. The way of information dissemination and the process of human cognition have undergone tremendous changes in the era of informatization. Based on the vision sensor digital image and the fusion association rule mining algorithm, this paper studies the informatization teaching mode, aiming to analyze the influence of the vision sensor digital image and the fusion association rule mining algorithm on the foreign language teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Image and Fusion Association Rule Mining Algorithm" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Security and Communication Network Has Retracted The Article...mentioning
confidence: 99%
“…Image and Fusion Association Rule Mining Algorithm" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Security and Communication Network Has Retracted The Article...mentioning
confidence: 99%